Indigenous Monikah Tajio Ethnic of Islamic Cultural Heritage at Kasimbar, Central Sulawesi - Malla, Hamlan Andi Baso; Yusuf, Khaeruddin; Yunus, Nur Rohim (Institut Agama Islam Negeri Madura, 2020)
This article objective to examine the monikah indigenous traditions for Kasimbar Tajio ethnic communities in Central Sulawesi. Qualitative method used in this research, data collection techniques of observation, interviews and document tracking non-structure. Technical analysis of data through data reduction, display data, verification data to generate conclusions and findings of the research results. Conclusion The study found that first; monikah custom comes from acculturation Mandar and Tajio ethnic culture in the tradition of marriage, second; monikah custom implementation of social value that affects personality Tajio ethnic communities in maintaining the values of brotherhood, family, respect for elders, unity and cooperation, maintain the pattern of interpersonal communication that is based on mutual respect in maintaining a harmonious relationship between human beings. third; monikah indigenous religious value that affects Islamic personality in performing worship to Allah (God), tawadhu’ attitude, moral education, purity and purification of the soul, ta’aruf and silaturrahmi.